Liraglutide Reduces Vascular Damage, Neuronal Loss, and Cognitive Impairment in a Mixed Murine Model of Alzheimer’s Disease and Type 2 Diabetes - Carranza-Naval, Maria Jose; del Marco, Angel; Hierro-Bujalance, Carmen; Alves-Martinez, Pilar; Infante-Garcia, Carmen; Vargas-Soria, Maria; Herrera, Marta; Barba-Cordoba, Belen; Atienza-Navarro, Isabel; Lubian-Lopez, Simon; Garcia-Alloza, Monica (Frontiers in Aging Neuroscience, 2021)
Alzheimer’s disease is the most common form of dementia, and epidemiological studies support that type 2 diabetes (T2D) is a major contributor. The relationship between both diseases and the fact that Alzheimer’s disease (AD) does not have a successful treatment support the study on antidiabetic drugs limiting or slowing down brain complications in AD. Among these, liraglutide (LRGT), a glucagon-like peptide-1 agonist, is currently being tested in patients with AD in the Evaluating Liraglutide in Alzheimer’s Disease (ELAD) clinical trial. However, the effects of LRGT on brain pathology when AD and T2D coexist have not been assessed. We have administered LRGT (500 μg/kg/day) to a mixed murine model of AD and T2D (APP/PS1xdb/db mice) for 20 weeks. We have evaluated metabolic parameters as well as the effects of LRGT on learning and memory. Postmortem analysis included assessment of brain amyloid-β and tau pathologies, microglia activation, spontaneous bleeding and neuronal loss, as well as insulin and insulin-like growth factor 1 receptors. LRGT treatment reduced glucose levels in diabetic mice (db/db and APP/PS1xdb/db) after 4 weeks of treatment. LRGT also helped to maintain insulin levels after 8 weeks of treatment. While we did not detect any effects on cortical insulin or insulin-like growth factor 1 receptor m-RNA levels, LRGT significantly reduced brain atrophy in the db/db and APP/PS1xdb/db mice. LRGT treatment also rescued neuron density in the APP/PS1xdb/db mice in the proximity (p = 0.008) far from amyloid plaques (p < 0.001). LRGT reduced amyloid plaque burden in the APP/PS1 animals (p < 0.001), as well as Aβ aggregates levels (p = 0.046), and tau hyperphosphorylation (p = 0.009) in the APP/PS1xdb/db mice. Spontaneous bleeding was also ameliorated in the APP/PS1xdb/db animals (p = 0.012), and microglia burden was reduced in the proximity of amyloid plaques in the APP/PS1 and APP/PS1xdb/db mice (p < 0.001), while microglia was reduced in areas far from amyloid plaques in the db/db and APP/PS1xdb/db mice (p < 0.001). This overall improvement helped to rescue cognitive impairment in AD-T2D mice in the new object discrimination test (p < 0.001) and Morris water maze (p < 0.001). Altogether, our data support the role of LRGT in reduction of associated brain complications when T2D and AD occur simultaneously, as regularly observed in the clinical arena.